Litigation in access to universal health coverage for children and adolescents in Brazil - Coelho Tavares da Silva, Suely; Tavares da Silva, Paulo Henrique; Antão de Medeiros, Robson; Barbosa do Nascimento, Vânia (Frontiers in Public Health, 2024)
Background Brazil’s Unified Health System (SUS) ensures universal, equitable, and excellent quality health coverage for all. The broad right to health, supported by the Constitution, has led to excessive litigation in the public sector. This has negatively impacted the financial stability of SUS, created inequality in children and adolescents’ access to healthcare, and affected communication between the healthcare system and the judiciary. The enactment of Law Number 13.655 on 25 April 2018, proposed significant changes in judicial decisions. This study aimed to investigate decision-making changes in health litigation involving children and adolescents following the implementation of the new normative model. Methods The study is cross-sectional, analyzing 3753 national judgment documents from all State Courts of Brazil, available on their respective websites from 2014 to 2020. It compares regional legal decisions before and after the promulgation of Law Number 13.655/2018. Data tabulation, statistical analysis, textual analysis, coding, and counting of significant units in the collected documents were performed. The results of data cross-referencing are presented in tables and diagrams. Results The majority (96.86%) of legal claims (3635 cases) received partial or total provision of what was prescribed by the physician. The Judiciary predominantly handled these cases individually. The analysis indicates that the decisions made did not adhere to the norms established in 2018. Conclusion Regional heterogeneity in health litigation was observed, and there was no significant variability in decisions during the studied period, even after the implementation of the new normative paradigm in 2018. Technical-scientific support was undervalued by the magistrates. Prioritizing litigants undermines equity in access to Universal Health Coverage for children and adolescents.